2011
DOI: 10.1097/ccm.0b013e318206b5a2
|View full text |Cite
|
Sign up to set email alerts
|

A novel antimicrobial and antithrombotic lock solution for hemodialysis catheters: A multi-center, controlled, randomized trial*

Abstract: The novel C-MB-P lock solution is well tolerated, significantly reduces the risk of catheter-related bloodstream infection, and provides protection comparable to heparin against patency failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
79
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 35 publications
1
79
1
3
Order By: Relevance
“…Because more recent studies using bundled care without antimicrobial locks have achieved CRBSI rates of #1 per 1000 catheter-days, can the use of antimicrobial locks further reduce CRBSI? Abbas et al performed an observational study of gentamicin-heparin versus heparin catheter locks, while Maki and Moran and their colleagues performed randomized controlled trials with gentamicin-trisodium citrate (citrate) and citratemethylene blue-methylparaben-propylparaben, respectively (17)(18)(19). All three studies achieved CRBSI rates of ,1 per 1000 catheter-days in their control groups and yet still showed a significant decrease in infection rates with their interventions (Abbas, Moran, and Maki et al reported rates of 0.62, 0.28, and 0.24 events per 1000 catheter-days, respectively).…”
mentioning
confidence: 99%
“…Because more recent studies using bundled care without antimicrobial locks have achieved CRBSI rates of #1 per 1000 catheter-days, can the use of antimicrobial locks further reduce CRBSI? Abbas et al performed an observational study of gentamicin-heparin versus heparin catheter locks, while Maki and Moran and their colleagues performed randomized controlled trials with gentamicin-trisodium citrate (citrate) and citratemethylene blue-methylparaben-propylparaben, respectively (17)(18)(19). All three studies achieved CRBSI rates of ,1 per 1000 catheter-days in their control groups and yet still showed a significant decrease in infection rates with their interventions (Abbas, Moran, and Maki et al reported rates of 0.62, 0.28, and 0.24 events per 1000 catheter-days, respectively).…”
mentioning
confidence: 99%
“…Other lock solutions with antimicrobial properties, such as citrate-and taurolidine-containing locks have showed mixed results regarding the impact on CLABSI incidence in dialysis patients. A novel catheter lock solution containing 7.0% sodium citrate, 0.15% methylene blue, 0.15% methylparaben, and 0.015% propylparaben (C-MB-P) was superior to standard heparin lock in a randomized controlled trial of 407 HD patients [24] . Thrombolytic locking solution has also shown promise in reducing bacteremias.…”
Section: Antimicrobial Lock Solutionsmentioning
confidence: 99%
“…Maki et al 23 have described a multicenter study in which a solution containing 0.24 M (7.0%) sodium citrate, 0.15% methylene blue, 0.15% methylparaben and 0.015% propylparaben (C-MB-P) was compared with heparin, reporting a significant reduction in…”
Section: Central Venous Cathetersmentioning
confidence: 99%